Does oxidative stress contribute to antituberculosis drug resistance? - Yew, Wing Wai; Chan, Denise P.; Chang, Kwok Chiu; Zhang, Ying (Journal of Thoracic Disease, 2019)
Escalation of drug resistance in Mycobacterium tuberculosis (MTB) furnishes a formidable challenge to the global control of tuberculosis (TB) (1). Delineation of the underlying mechanisms of anti-TB drug resistance is germane to the discovery of strategies in tackling this worldwide health care crisis. Aside from the development of new anti-TB drugs to circumvent the drug resistance scenarios to improve patient treatment outcomes, it appears pertinent to explore whether modulation of host factors or responses could help to ameliorate the probability of drug-resistant TB.